Edukasi Legalitas Usaha bagi UMKM Kabupaten Tangerang Bersama Bank Indonesia dan Lembaga Pemberdayaan Ekonomi Rakyat - Hasna, Shofwatun; winanti, winanti; Goestjahjanti, Francisca Sestri; Nurasiah, Nurasiah; Himmy'azz, Istajib Kulla; Suwita, Jaka; Kumoro, Dwi Ferdiyatmoko Cahya; Kamar, Karnawi; Supriyanto, Supriyanto; Adiyanto, Adiyanto (IAHN Gde Pudja Mataram, 2024)
There are still many MSMEs in Tangerang Regency who do not have business legality which has an impact on aid, grants, taxes and various banking-related matters. The aim of the outreach is to provide understanding and socialization regarding business legality for MSME actors. There were 200 participants in the activity including MSMEs, lecturers and students. As a result of the socialization, it is hoped that MSME actors in Tangerang Regency will make business legality a general requirement and will be useful and profitable for business owners. The results of monitoring and evaluation using interviews with several participants stated that everyone was satisfied and happy with this education. The hope is that after this socialization and education activity, MSME players will be able to manage and have business legality